Reflections on a la Carte Issues in English Language Teaching (Journal of NELTA, 2024)
I have taught English literature, English language, and linguistics for fifty years now. My experience as a teacher, teacher trainer, and researcher has given me some personalized insights into issues such as the difference between teaching children and teaching adults, the evolution of the author of this paper as a teacher, the role of technology in teaching, paradigm shifts in English language teaching, the deterioration in the quality of research, the perceptions of the role of the mother tongue, the impact of the linguistic hegemony on English language teaching, and the literature-language divide. The present paper attempts to understand the influence of these issueson language policy, language teaching, language learning, materials production, evaluation, assessment, etc.